2018
DOI: 10.1002/mrm.27207
|View full text |Cite
|
Sign up to set email alerts
|

An analytic expression for the ultimate intrinsic SNR in a uniform sphere

Abstract: The proposed formula enables rapid and direct calculation of UISNR in the central region of a sphere. The resulting UISNR value may be used, for example, as an absolute reference to assess the performance of head coils with spherical phantoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
2
20
0
Order By: Relevance
“…Our results demonstrated that the signal‐only optimal and ideal current patterns were equivalent for a central voxel (Figure ). The absence of dark mode current patterns (Figure ) can be explained by the fact that only a single current mode contributes to the signal sensitivity at the center of a sphere, limiting the degrees of freedom to simultaneously minimize sample noise. Phase advancement in the ideal and signal‐only current patterns in the presence of HPM (Figures and ) indicate that the current pattern optimization has accounted and compensated for the phase delay encountered by the signal propagating through the HPM layer.…”
Section: Discussionmentioning
confidence: 99%
“…Our results demonstrated that the signal‐only optimal and ideal current patterns were equivalent for a central voxel (Figure ). The absence of dark mode current patterns (Figure ) can be explained by the fact that only a single current mode contributes to the signal sensitivity at the center of a sphere, limiting the degrees of freedom to simultaneously minimize sample noise. Phase advancement in the ideal and signal‐only current patterns in the presence of HPM (Figures and ) indicate that the current pattern optimization has accounted and compensated for the phase delay encountered by the signal propagating through the HPM layer.…”
Section: Discussionmentioning
confidence: 99%
“…Approaching the problem from the point of view of determining uiSNR, Lee et al 13 demonstrated that only one divergence‐free mode contributes to the MR signal at the center of a sphere with uniform electrical properties, which led to the derivation of a precise analytical expression for the uiSNR in the center of a sphere. The returned expression is identical to the previous Hoult's result (Equations 48 and 6 in the two articles, respectively), thus proving that this SNR formula in fact can be considered the uiSNR at the center of a sphere of uniform properties.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, their shape was identical for the central voxel, consisting of distributed current loops precessing at the Larmor frequency around the direction of the main magnetic field (Video S1). This was expected, since only one mode survives at the center of the sphere, 24 and in both cases its role is to closely track spins precessing at the voxel of interest. The only difference is the opposite direction of the precession of the current loops, which accounts for the fact that for OPTXE it is the transmit sensitivity that is maximized, whereas for UISNR it is the receive sensitivity.…”
Section: Discussionmentioning
confidence: 93%
“…As a result, the optimal RF shimming weights are not equal in the two cases, yielding different distributions of the net magnetic and electric field. The shape and amplitude of the ICP associated with OPTXE and UISNR for the same voxel are also different, except at the center of the object, where they are dominated by one mode 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation